Phase-coded microwave signals generation using a dual parallel construction including two phase modulators. (September 2018) - Wang, Fei; Yu, Qiong; Gu, Jun; Lu, Youxi
Highlights: A photonic approach to realizing binary phase-coded microwave signal generation was proposed. The binary phase-coded microwave waveform with a π phase shift was achieved. The proposed approach exhibits a good pulse compression performance. Abstract: A photonic approach to realizing binary phase-coded microwave signal generation using a dual parallel construction including two phase modulators (PMs) was proposed and demonstrated. A beam CW is split into two beams light wave with equal power in the dual parallel construction, one beam is modulated in a PM driven by a radio frequency (RF) microwave signal in the upper arm, and the other beam is modulated by another PM driven by a binary coding electrical pulse sequence in the under arm, then the two phase-modulated beams combine and interfere. When the interference light field is send to a high-speed photodetector (PD) for beating, 2 Gbit/s binary phase-coded 10 GHz and 2.5 Gbit/s phase-coded 20 GHz microwave waveform with a π phase shift was respectively achieved, and corresponding pulse compression ratio is 20 and 16.5, respectively. The obtained phase-coded microwave signals exhibit a good pulse compression performance, which can find potential applications in modern radar systems and wireless communications.